2005
DOI: 10.1073/pnas.0503998102
|View full text |Cite
|
Sign up to set email alerts
|

In search of an auditory engram

Abstract: Monkeys trained preoperatively on a task designed to assess auditory recognition memory were impaired after removal of either the rostral superior temporal gyrus or the medial temporal lobe but were unaffected by lesions of the rhinal cortex. Behavioral analysis indicated that this result occurred because the monkeys did not or could not use long-term auditory recognition, and so depended instead on short-term working memory, which is unaffected by rhinal lesions. The findings suggest that monkeys may be unabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
220
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(241 citation statements)
references
References 38 publications
16
220
5
Order By: Relevance
“…Further, if WM does indeed depend on reactivation of a stimulus representation stored in LTM, then the absence of auditory WM could well be due to the monkey's inability to achieve long-term storage in the auditory modality. Although the above interpretation provides a cohesive account of our findings, with the apparent absence of auditory WM in the present study and of auditory LTM in the earlier one (12) reinforcing each other, there are other possible explanations of the results that need to be considered. For example, monkeys might actually have both forms of auditory memory, but their WM system may not be capable of maintaining LTM traces in an active state in the face of interference.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Further, if WM does indeed depend on reactivation of a stimulus representation stored in LTM, then the absence of auditory WM could well be due to the monkey's inability to achieve long-term storage in the auditory modality. Although the above interpretation provides a cohesive account of our findings, with the apparent absence of auditory WM in the present study and of auditory LTM in the earlier one (12) reinforcing each other, there are other possible explanations of the results that need to be considered. For example, monkeys might actually have both forms of auditory memory, but their WM system may not be capable of maintaining LTM traces in an active state in the face of interference.…”
Section: Discussionmentioning
confidence: 63%
“…S1). Because of the known difficulty monkeys have in acquiring and applying the rule for auditory DMS (12,(18)(19)(20)(21)(22), we simplified task requirements by requiring the animal to (i) remember a single sample stimulus for 1 s, and (ii) respond at test to an identical match stimulus and withhold responding to a nonmatch that, importantly, always belonged to a stimulus category other than the sample's category. The only To whom correspondence may be addressed.…”
mentioning
confidence: 99%
“…There are considerable anatomical data that the midventrolateral prefrontal cortex (and particularly area 45) is extensively connected with the superior temporal gyrus and the nearby dorsal bank of the superior temporal sulcus (through the extreme capsule and the arcuate fasciculus) and also with the inferior parietal lobule (area PG) (via the second branch of the superior longitudinal fasciculus) (14, 16-18, 20, 37). The superior temporal region of the primate brain is critical for the encoding and short-term maintenance of auditory information (32,33,38), whereas the caudal superior temporal gyrus and the adjacent parabelt region in the caudal superior temporal sulcus entering the inferior parietal lobule are involved in the spatial aspects of auditory coding (34,36). Indeed, a recent study using transcranial magnetic stimulation has shown that the caudal part of the superior temporal gyrus, close to the inferior parietal lobule, is involved in auditory localization to a greater extent than the more rostral temporal region (39).…”
Section: Discussionmentioning
confidence: 99%
“…† with this dual-tract system extending ventrally into the middle and inferior temporal gyri as well as dorsally into the ventral premotor gyrus. By comparison, the arcuate fasciculus in monkeys is a primitive one (7,8,11,62), providing a possible explanation for the monkey's apparent inability to store the representations of fluctuating acoustic stimuli in long-term memory (5). Conversely, the large size and complexity of this dual tract in humans may have enabled long-term memory for speech sounds by providing the auditory system with an input that transforms an intractable, fluctuating, acoustic stimulus into an integrated acoustic/oromotor sequence that can be stored for subsequent recognition.…”
Section: Discussionmentioning
confidence: 99%
“…In vision and touch, monkeys master the rule for one-trial recognition memory extremely rapidly, within several daily sessions (1,2); and once they have learned the rule, it can be shown that they have stimulus-retention thresholds (performance at 75% accuracy) of 10-20 min after viewing or palpating a novel stimulus for only 1-2 s (3,4). In audition, by contrast, monkeys acquire the rule for one-trial memory exceedingly slowly, requiring a full year or two of training before they can master it, if they succeed at all; and if they do succeed, their stimulus-retention thresholds are found to extend no longer than 30-40 s after stimulus presentation (5). This marked disparity in mnemonic ability across sensory modalities suggests that, in audition alone, monkeys seem unable to store stimulus representations in long-term memory (LTM) and, consequently, appear to be limited mnemonically to the time period covered by short-term memory.…”
mentioning
confidence: 99%